No Mere Reflection: Mirrors as Windows on Russian Culture - Julia Chadaga (Studies in 20th & 21st Century Literature, 2010)
This essay traces the development of mirror use in Russia from the medieval period to the modern day with particular attention to the dynamic interplay between the utilitarian and symbolic functions of this object. I examine how the discourse around mirrors in Russia was shaped by a preoccupation with border-crossing and identity that is distinctive to Russian culture as well as by mirror lore from other world traditions; and I demonstrate that the presence of mirrors shaped the production of imaginative literature in profound ways. The essay focuses on several key functions of the Russian mirror: as a site of self-creation and social interaction, as illusionistic décor, and as a tool for obtaining knowledge. In discussing human responses to mirror reflections, as documented in written texts, folklore, and film, my essay begins with personal mirrors in private spaces that conveyed the features of solitary beholders, and then moves outward to consider larger objects in public spaces, from street mirrors to glass skyscrapers, that were seen by multitudes and generated countless reflections in both the literal and the figurative sense.
Keywords: mirror; mirror use in Russia; Russia; Russian history; medieval period; modern day; identity; tradition; imaginative literature; self-creation; social interaction; private spaces; texts; folklore; film; public spaces